1994
DOI: 10.1159/000204177
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Phagolysosomal Fusion of Peripheral Blood Monocytes from Patients with Thalassemia Major

Abstract: We evaluated the phagolysosomal fusion of peripheral blood monocytes from 15 patients with thalassemia major and 10 thalassemia major carriers using a cytomorphological method with acridine orange as fusion marker. The mono-cyte phagolysosomal fusion of thalassemic patients was decreased (49.6 ± 8.6%, mean ± SD) and differed significantly (p < 0.05) from those of carriers and normal controls (65.7 ± 11.4% and 74.6 ± 5.7%, respectively). In vitro deferoxamine partially improved monocyte phagolysosomal fusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In the study of humoral immunity was found inappropriate secretion of immunoglobulins, which was expressed in increased levels of IgG, IgM, and IgA [19,23,25,34,35] and depressed functioning of the complement system reducing the levels of C3 and C4 complement components [7,19,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of humoral immunity was found inappropriate secretion of immunoglobulins, which was expressed in increased levels of IgG, IgM, and IgA [19,23,25,34,35] and depressed functioning of the complement system reducing the levels of C3 and C4 complement components [7,19,34].…”
Section: Introductionmentioning
confidence: 99%